An Examination of Perceived Quality, Satisfaction, and Loyalty Relationship: Applicability of Comparative and Noncomparative Evaluation - Darsono, Licen Indahwati; Junaedi, C. Marliana (Gadjah Mada International Journal of Business, 2006)
This paper evaluates alternative measurement approaches to investigating the relationship amongst perceived quality, customer satisfaction, and loyalty. The authors define and measure the constructs within a relative attitudinal framework and compare these results to a noncomparative or individual evaluation of brands. In addition, loyalty is measured by and defined as a behavioral and attitudinal loyalty. The object of this research is teh botol whilst the subjects are undergraduate students in Surabaya and Yogyakarta. The proposed model, with satisfaction as a mediator between quality and loyalty, is found to be an acceptable representation of data across three brands of teh botol and for both comparative and noncomparative evaluation. The use of relative attitude, however, indicates a much stronger relationship amongst perceived quality, satisfaction, and loyalty than the attitude towards a brand when they are performed in individual evaluation. With respect to predictive ability, this studyâs findings suggest that comparative evaluation has higher degree of applicability than does noncomparative evaluation.